Methodology for improving aerobic-anaerobic endurance in the especial preparation of the 15-16 years cyclists from Ormani Arenado sport school in Pinar del Río - Cira Hernández-González; Leduam Silva-Méndez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
Endurance is one of the determining training management of the cycling athletes´ sport results according to the specialty or event that they represent. Among this physical capacity variants we pay special attention to the mix endurance training in the special preparation stage because it is not being applied, element that it is considered one of the causes of the athletes' low performance. Taking into account this insufficiency it's proposed an exercise methodology to improve aerobic-anaerobic endurance in the special preparation of the 15-16 years cyclists from Ormani Arenado sport school in Pinar del Río, which intend to solve the scientific problem given in the report. During the exploratory study it was detected as mains weaknesses, the absolute prominence of the long duration continuo work, the use of continuo methods to develop this capacity, excluding the fartlek exercises. On the other hand, it was checked that they don't develop the aerobicanaerobic endurance through mileage fragmentation using intermittent methods, mainly repetitions and intervals, among other difficulties that are referred in the work. They were corroborated through different research instruments application, such as observation, interview and measuring.